Analisis Kepuasan Kerja Pegawai Di Kantor Inspektorat Kabupaten Mandailing Natal - Novaal Novita; Ade Fay Eve; Angellina Joel (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The purpose of this study was to determine the level of job satisfaction of employees at the Mandailing Natal District Inspectorate Office. To obtain the expected analysis results, in this study a descriptive method was used through a quantitative approach and then verified. From the results of data analysis and discussion, it was concluded that the job satisfaction level category of the Mandailing Natal District Inspectorate employee was